3379 Associations between Diabetes Mellitus and Sublingual Microvascular Disease: A Prospective Cross-Sectional Study. (27th March 2019) - Smilowitz, Nathaniel R; Windheim, Joseph; Simon, Elias; Reynolds, Harmony
Abstract : OBJECTIVES/SPECIFIC AIMS: Diabetes mellitus (DM) is a risk factor for the development of microvascular complications. We sought to determine the association between diabetes mellitus status and microvascular circulatory disease, as measured in the sublingual capillary bed. METHODS/STUDY POPULATION: We prospectively recruited adults with cardiovascular (CV) risk factors or established CV disease, with and without DM, who were referred for invasive coronary angiography at an urban tertiary care medical center. All participants underwent non-invasive sublingual sidestream darkfield microscopy. The primary outcome was the perfused boundary region (PBR), a measure reflecting the extent to which red blood cells (RBC) penetrate the sublingual glycocalyx in vessels between 5 and 25 µm in width. RESULTS/ANTICIPATED RESULTS: 57 participants were enrolled. The mean age was 66.1 ± 11.1 years and a majority of participants (66%) were men. DM was present in 18 (31.6%) participants. Sublingual PBR measurements were not different between participants with and without DM overall (1.93µm vs. 1.96µm, p=0.63) or in vessels with high flow (1.48µm vs. 1.59µm, p=0.08). No differences in capillary RBC filling (72.9% vs 73.0%, p=0.95) or perfused microvascular density (3112 vs. 3236 µm/mm2, p=0.32) by DM status were observed. DISCUSSION/SIGNIFICANCE OF IMPACT: In a population of adults with CV risk factors or disease, DM was not associated with impaired sublingual microvascular glycocalyx. Additional investigation into diabetes-induced microvascular impairment is warranted.